Building a Leader Framework for Post-Pandemic Response Expertise for Higher Education Future Reality - Makina, Antonia (Innovare Journal of Education, 2024)
A successful future for higher education is dependent on the level of preparedness to manage future crises that are no longer linear processes in the best way possible. The severe disruption of academic progress post-COVID-19 across the globe brought a growing sense of chaos in the education system. This forced education institutions to adopt a rapid re-design of institutional strategic systems that called for different kinds of responses in different contexts because previous successful leadership approaches often fail in crisis situations. However, the challenges brought about by the chaos have positively presented humanity with many opportunities to re-think and re-engineer a new way of doing business. Therefore, this paper designs and develops a post-pandemic conceptual model that is an approach to crisis management, quick decision-making, and quick problem-solving to enable general adaptation to future pandemics. Through a developmental research design and a comprehensive literature review, an adaptive emergence response cycle (AERC) was developed and built around the theory of chaos, the reflective practitioner theory, using the adaptive approach. One potential benefit of the post-pandemic response model was the creation of an emergency response equation that was best suited for the post-pandemic crises. This model allows higher education management to be protected by planning generalizable futuristic crisis models.